Differential microRNA Expression in Porcine Endometrium Involved in Remodeling and Angiogenesis That Contributes to Embryonic Implantation - Hong, Linjun; Liu, Ruize; Qiao, Xiwu; Wang, Xingwang; Wang, Shouqi; Li, Jiaqi; Wu, Zhenfang; Zhang, Hao (Frontiers in Genetics, 2019)
Background: In western pig, up to 30% of embryonic loss happens during early pregnancy, and the majority of embryonic loss happens during implantation. In this period, the maternal recognition of pregnancy begins to occur and the blastocysts undergo dramatic morphological changes. The maternal uterine environment plays an important role in the process of implantation in pigs. Erhualian pig (ER), one of Chinese Taihu pig breeds, is known to have the highest litter size record in the world. Experiments demonstrated that the greater embryonic survival on GD12 in Taihu pig was the important factor contributed to enhanced litter size, and this was controlled very largely by maternally genes. In this study, endometrial samples were collected from pregnant Landrace × Large White (LL) sows (parity 3) and Erhualian sows (parity 3) on GD12. The expression profiles of miRNAs in endometrium were compared between Erhualian and LL using Solexa sequencing technology. Results: A total of 288 miRNAs were identified in the pig endometrium, including 202 known miRNAs and 86 novel miRNAs. KEGG pathway analysis revealed that highly abundant miRNAs might affect endometrial remodeling. In the comparison of these two breeds, 96 known miRNAs were identified to be differentially expressed between the two groups (including 78 up-regulated and 18 down-regulated miRNAs in RE compared with LL). Bioinformatics analysis showed that the target genes of some differentially expressed miRNAs were involved in pathways related to angiogenesis, proliferation, apoptosis and tissue remodeling, which play critical roles in implantation by regulating endometrial structural changes and secretions of hormones, growth factors and nutrients. Furthermore, our results demonstrated that IGF1 protein expression was directly inhibited by miR-206, the lower expression of miR-206 in Erhualian than in LL might facilitate angiogenesis of endometrium during peri-implantation. Conclusions: The identification of miRNAs that are differentially expressed in endometrium between Erhualian and LL will contribute to our understanding of the role of miRNAs in embryonic implantation and the molecular mechanisms of the greater embryonic survival in Chinese Taihu pigs.